HEALTH LEVEL OF SHARIA COMMERCIAL BANKS STUDY WITH RISK BASED BANK RATING (RBBR) APPROACH FOR THE YEARS 2018-2022 - Azizah, Afiq; Rois, Muhammad; Rikawati, Rikawati (Politeknik Negeri Semarang, 2024)
This reseacrch aims to analyze the health level of Islamic commercial banks registered with the Financial Services Authority for the period 2018-2022. The sampling technique was carried out using purposive sampling technique. Based on the sampling criteria, 6 Islamic commercial banks were obtained that could be used as research samples. The research method used is the Risk Based Bank Rating (RBBR) method including risk profile, good corporate governance, earning and capital factors. The results showed that during the 2018-2022 period, the Islamic commercial bank that had the best health level the